La calidad en el sector servicios: El reto para la competitividad turística del ecuador, experiencias de su aplicación - Ocaña Zambrano, Walter Omar (2018)
The quality of the current commercial dynamics becomes the main differentiating factor in an increasingly competitive market, even more in the services sector, where the growing emergence of new emerging destinations and the constant diversification of Tourist products, has developed a thin line between the offer and the decision of purchase or return by the client. In Ecuador, this is an element that has become moreand more relevant in recent years, the implementation of quality standards and models has been concentrated mainly in the establishments oriented towards a receptive market, as well as in the main Destinations in the country, however, as a public policy aimed at promoting tourism quality is being put in place, the language of quality has been progressively included in other territories and markets. This work includes some experiences obtained in the application of quality in the services sector, as part of a process of formation and articulation with the business sector, mainly in small and medium-sized tourism companies and hospitality.